(untitled) (Per Musi, 2012)
This article, a summary of the Master thesis (2008), discusses the observation and evaluation of physical problems presented by six Bachelors students of the Music School of UFMG (Brazil), in their violin practice. It is hoped that this research draws the attention of violinists and violin teachers to the importance of body consciousness whilst performing the instrument, emphasizing the need to maintain the symmetry and body relaxation of those parts involved in the act of playing the violin.